2020
DOI: 10.1152/ajpheart.00302.2019
|View full text |Cite
|
Sign up to set email alerts
|

Activin type II receptor ligand signaling inhibition after experimental ischemic heart failure attenuates cardiac remodeling and prevents fibrosis

Abstract: Myostatin (MSTN) is a transforming growth factor (TGF)-β superfamily member that acts as a negative regulator of muscle growth and may play a role in cardiac remodeling. We hypothesized that inhibition of activin type II receptors (ACTRII) to reduce MSTN signaling would reduce pathological cardiac remodeling in experimental heart failure (HF). C57BL/6J mice underwent left anterior descending coronary artery ligation under anesthesia to induce myocardial infarction (MI) or no ligation (sham). MI and sham animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
4
22
0
Order By: Relevance
“…Of interest, ACVR2B/Fc administration was able to completely preserve cardiac function in the presence of metastatic CRC. In support of this observation, others have recently demonstrated that the myostatin/ACVR2B signalling is up‐regulated in the heart of patients with heart failure 75 and that targeting ACVR2B can improve cardiac function in models of ageing, ischaemia, and myocardial infarction, thereby implicating activin signalling as a negative input on cardiac function 76–78 . To our knowledge, ours is the first report providing evidence that ACVR2B could represent a potent therapeutic target to preserve cardiac function in the occurrence of metastatic CRC.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Of interest, ACVR2B/Fc administration was able to completely preserve cardiac function in the presence of metastatic CRC. In support of this observation, others have recently demonstrated that the myostatin/ACVR2B signalling is up‐regulated in the heart of patients with heart failure 75 and that targeting ACVR2B can improve cardiac function in models of ageing, ischaemia, and myocardial infarction, thereby implicating activin signalling as a negative input on cardiac function 76–78 . To our knowledge, ours is the first report providing evidence that ACVR2B could represent a potent therapeutic target to preserve cardiac function in the occurrence of metastatic CRC.…”
Section: Discussionsupporting
confidence: 61%
“…In support of this observation, others have recently demonstrated that the myostatin/ACVR2B signalling is up-regulated in the heart of patients with heart failure 75 and that targeting ACVR2B can improve cardiac function in models of ageing, ischaemia, and myocardial infarction, thereby implicating activin signalling as a negative input on cardiac function. [76][77][78] To our knowledge, ours is the first report providing evidence that ACVR2B could represent a potent therapeutic target to preserve cardiac function in the occurrence of metastatic CRC. Interestingly, cardiac function is preserved despite no effects in terms of whole-heart size, LV mass, nor major impact on regulators of muscle growth, thereby suggesting that signalling through ACVR2B is not critical in regulating heart size in metastatic CRC.…”
Section: Discussionmentioning
confidence: 81%
“…However, being a strong predictor of frailty, disability, and mortality sarcopenia occurs in patients with HFrEF in results of abundant molecular mechanisms including Smad2/3 signaling [ 101 , 104 ]. Probably, these controversies in the protective ability of myostatin relate to etiology (ischemic or nonischemic) of HF [ 105 , 106 ].…”
Section: Myokines In Hf Myopathymentioning
confidence: 99%
“…This was achieved using a soluble ACVR2B decoy receptor 19 or by inhibiting ACTRII/TGFBR signaling 47 , respectively. Interestingly, the latter presented an underlying mechanism we identified ourselves during transcriptome analysis in mice: the mentioned up-regulation of Atp2a2 in Mstn Ln/Ln mice with concurrent down-regulation in WT mice, which was paralleled by up-regulation of SERCA2a (translational product of Atp2a2 ) in the setting of cardioprotection after myocardial infarction in mice 47 . Additionally, Zhu et al 48 had previously linked SERCA2a activity to p38 MAPK signaling: in 2017, they studied the effects of IR on rat cardiac function.…”
Section: Discussionmentioning
confidence: 99%